2018
DOI: 10.2478/arsm-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Working in Shifts and the Metabolic Syndrome: Epidemiological Evidence and Physiopathological Mechanisms

Abstract: The Metabolic syndrome (MetS) is considered as an association of the abdominal obesity, abnormal metabolism of the lipids and glucose (high level of triglycerides, low level of HDL-cholesterol and high level of glycemia) and high values of blood pressure, determined by an underlying mechanism of insulin resistance. As a result of environmental-gene interaction, MetS is associated with unhealthy nutrition, smoking, alcohol abuse, lack of physical activity, shorter sleep duration and desynchronization of the cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In the present study, we found no significant difference when comparing the proportion of rotational (8 h) and day-shift workers with metabolic syndrome. Working shift and progression of metabolic syndrome has been shown as epidemiological evidence of physiopathological mechanisms [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found no significant difference when comparing the proportion of rotational (8 h) and day-shift workers with metabolic syndrome. Working shift and progression of metabolic syndrome has been shown as epidemiological evidence of physiopathological mechanisms [ 38 ].…”
Section: Discussionmentioning
confidence: 99%